Formulasi Sabun Cair dari Ekstrak Batang Nanas (Ananas comosus. L ) untuk Mengatasi Jamur Candida albicans - Anggraini, Deni; Rahmides, Wiwik Sri; Malik, Masril (Jurnal Penelitian Farmasi Indonesia, 2013)
A study on antifungal effect of liquid soap formulation of extract of pineapple stem (Ananas comosus L) has been carried out towardsCandida albicans. Three different concentrations of extract 3; 5 and 7%, were formulated as liquid soap using TEA, stearic acid andglycerine as its soap bases. Several evaluations were examined on the liquid soap formulation including organoleptic examination, determinationof relative density, viscosity, foam test, pH test, and skin irritation test. While antifungal effect test of the obtained formulations was testedon PDA medium. The result revealed that extract of pineapple stem was successfully formulated and physically stable in liquid soap form.The antifungal effect test showed that formula with 7% concentration of extract demonstrated the strongest effect with 21.3 mm diameterof inhibition towards Candida albicans.